ANALISIS SALURAN PEMASARAN PISANG AMBON DI KECAMATAN CEMPAKA KABUPATEN OKU TIMUR - Neng Karmila, Tiyas Murtiningsih, Leni Sabrina, Muhammad Andri Zuliansyah, (JASEP, 2024)
Ambon bananas are one of the leading fruit commodities in Indonesia. This research aims to analyze marketing channels and marketing margins for Ambon bananas in Cempaka District, East OKU Regency. The research location was determined deliberately. The research method used in this research is the survey method. The sampling method used was a purposive method, taken from 30 Ambon banana farmers in Cempaka District with the criteria for land area being 0.25 to 1 hectare. Based on the research results, there are two marketing channels for Ambon bananas in Cempaka District, East OKU Regency, namely marketing channels I and II. In Marketing Channel I, a marketing margin of IDR 37,000.00 is obtained, and in marketing channel II it is IDR 35,000.00.